PERSISTENT MULLERIAN DUCT SYNDROME - Zaidi, Syed Aizaz Hussain; Medhat, Naila; Ahmad, Danial; Ali, Amir; Shah, Mir Zaman; Hussain, Syed Mukarram (Journal of Ayub Medical College Abbottabad, 2021)
Persistent Mullerian Duct Syndrome is extremely rare. Our patient, a 32 years old male, with history of orchidectomy presented with mass abdomen. He was initially diagnosed with seminoma and subsequently treated with chemotherapy. Biopsy of the mass showed germ cell tumour and MRI abdomen revealed female rudimentary organs confirmed on per operative and later on histopathology. Karyotype was 46 XY.